THE FACTOS OF TOURISTS DECISION MAKING IN THE NATURAL TOURISM OF ALAM MAYANG PEKANBARU - Putty Mayangsari; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of conduching this research is to know factors – factors decision making visitor and tourist before the visit Alam Mayang Pekanbaru City. The research use descriptive mothode to analyze the prooblems. The sampel inside this research are 100 respondence by using accidental sampling. And then technique to collected data in this research are using observation, questionnaire, interview, and documentation. And it was using likert scale to know the length of intervals. Factors that influence the decision making process visitor at Alam Mayang, internal factors, external factors, and situational factors (Etta dan Sopiah, 3013). From the result of research, according to responses by tourist the factor internal is a very determining faktor in the proses of decision making to visit Alam Mayang tourism object.Key word : decision making factors, tourist, tourism object